Predicting scientific research output at the University of KwaZulu-Natal - Murray, Mike (South African Journal of Science, 2017)
Academic members of staff at the University of KwaZulu-Natal (UKZN) are expected to publish in research journals that have been accredited by the South African based Department of Higher Education and Training. However, some members of staff have chosen to focus solely on the teaching aspect of their careers and as a result they have no publication record. In this study, a set of per annum productivity unit counts was calculated for every academic at UKZN. Because it is possible for a publishing academic to also record a zero count for a given year, it is necessary to develop an appropriate methodology that can distinguish this zero count from one that will always be recorded by a non-publishing academic. By fitting a zero-inflated Poisson model to the data, specific factors can be identified that separately drive the non-publishing and publishing processes at UKZN. In particular, having a PhD and working in a large school has a significant impact on improving the research output of a publishing academic. If UKZN wants to become a research-focused university, non-publishing academics should be encouraged to under take a PhD degree.